Does standalone phacoemulsification lower intraocular pressure in glaucomatous eyes? A systematic review and meta-analysis - Osama Hussein (21301202) (2025)
We evaluated the effect of phacoemulsification on intraocular pressure (IOP) and the reduction of glaucoma medications in patients with glaucoma. Our protocol was registered in PROSPERO (CRD42024533437). We conducted a systematic search in PubMed, Scopus, Cochrane Central Register of Controlled Trials (CENTRAL), and Web of Science for randomized clinical trials (RCTs) with at least 10 eyes and a 12-month minimum follow-up. Risk of bias assessment was performed using the Cochrane risk-of-bias tool. A random-effects model meta-analysis was used, and heterogeneity was assessed using Cochran’s Q and I² statistics. We included 41 RCTs with a total of 2315 eyes in the phacoemulsification-alone group. In ACG patients, the pooled effect showed a percentage of IOP reduction (IOPR%) of 35.22% with a mean IOP reduction of −9.51 mmHg, p< 0.001 at 12 months, and an IOPR% of 27.47% with a mean reduction of −6.37 mmHg, p < 0.001 at 24 months. For OAG patients, the pooled effect showed an IOPR% of 18.94% with a significant absolute change of −4.35 mmHg, p < 0.001 at 12 months, and IOPR% of 16.95% with an absolute IOP change of −3.83 mmHg, p < 0.001 at 24 months. In ACG patients, medication use decreased by 67.13% at 12 months and 51.58% at 24 months (p < 0.001 for both), while in OAG patients, the reduction was 45.52% at 12 months and 50.19% at 24 months (p < 0.001). In conclusion, standalone phacoemulsification significantly lowers IOP and reduces the need for glaucoma medications in patients with glaucoma. Other Information Published in: Eye License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41433-025-03927-7